2020
DOI: 10.5114/kitp.2020.97254
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of metastatic diseases to the lung

Abstract: Introduction: The problem of treating secondary cancer is very controversial. Huge progress in its treatment began in the 1970s with the introduction of chemotherapy. In the surgical aspect Pastorino's work published in 1997 was a milestone. To this day, most authors cite its research results. Aim: The task is to answer the question what tactics to follow in the surgical treatment of patients with secondary cancer affecting the respiratory system. Material and methods: Retrospective studies were conducted on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Further analysis revealed that the number and total diameter of metastases in the three subgroups were smaller than those in the other corresponding subgroup, and there was a significant difference in the total diameter of metastases between wedge resection and lobectomy (P<0.05). One study showed that the number and size of metastases significantly influenced prognosis (21). Therefore, we believe that better survival may be associated with a lower tumor load and not with differences in surgical treatment.…”
Section: Discussionmentioning
confidence: 81%
“…Further analysis revealed that the number and total diameter of metastases in the three subgroups were smaller than those in the other corresponding subgroup, and there was a significant difference in the total diameter of metastases between wedge resection and lobectomy (P<0.05). One study showed that the number and size of metastases significantly influenced prognosis (21). Therefore, we believe that better survival may be associated with a lower tumor load and not with differences in surgical treatment.…”
Section: Discussionmentioning
confidence: 81%
“…LN dissection is not a routine procedure for metastatic lung cancer [ 19 ]. However, the incidence of LN metastasis in this cancer ranges from 12 to 19%, and the negative impact of LN metastasis on survival has been demonstrated [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 5-year survival rate is 58.3% in the absence of LN metastasis and 24.8% with metastasis [ 18 ]. However, LN assessment is not routinely performed for patients with lung metastasis [ 19 ]. Only suspicious LNs are dissected during lung metastasectomy [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our research, the rate was around 7%, of which around 30% were not related to the surgery. The risk of perioperative death in the study group was 0.5% [ 3 , 4 ]. For the purposes of the present study, the PFS time was defined as the appearance of new lung lesions after metastasectomy or the date of death or the date of completion of the observation assuming that the patient was alive up to that date.…”
Section: Discussionmentioning
confidence: 99%
“…Here, too, often erroneous results of publications dealing with this problem are produced. In our previous studies, after creating two comparable groups of patients, we found longer survival in patients without relapse after metastasectomy (median survival 71 months without relapse versus 36 months with relapse) [ 3 , 4 ]. Subsequent metastasectomies are directly related to disease progression.…”
Section: Introductionmentioning
confidence: 99%